Essential oil composition and bioinformatic analysis of Spanish broom (Spartium junceum L.) - Younes Ghasemi; Hamed Abedtash; Mohammad Hossein Morowvat; Abdolali Mohagheghzadeh; Shirin Ardeshir-R (Shiraz University of Medical Sciences, 2015)
The essential oil, isolated by hydrodistillation from fresh flowers of Spartium junceum L. collected from medicinal plant garden in Shiraz faculty of pharmacy, near Shiraz, Fars, Iran, was investigated by Gas chromatography-Mass spectrometry (GC/MS) method. The GC/MS analysis of the oil revealed the presence of 30 constituents, of which Linalool (26.18%), Tetradecanoic acid (22.83%), Camphor (13.50%), and Dodecanoic acid (13.09%) were the major, constituting altogether almost 75.60% of total composition. This is the first report of linalool as a major compound in S. junceum oil composition.For studying of 18S rRNA gene, genomic DNA content was extracted and PCR procedure was done. Sequence similarity searches were done using NCBI database and CLC sequence viewer software. The result of PCR blasted with other sequenced genes in NCBI showed 98 % similarity to the 18S small subunit rRNA of Pisum sativum (Fabaceae) and Phaseoleae environmental samples of Elev and Amb clones. The phylogenetic relationships among 71 previously reported sequences of ribosomal encoding genes from plants and this novel sequence was investigated too.